INTRAOPERATIVE REASONS FOR CONVERSION OF LAPAROSCOPIC CHOLECYSTECTOMY TO OPEN SURGERY (SYSTEMATIC REVIEW) - Khakimov M.Sh.; Karimov R.A.; Jasmin Sabanovic; Karim Belhaj; Bijendra Patel (Central Asian Journal of Medicine, 2023)
Three electronic databases were searched to identify the studies reporting intraoperative risk factors of conversion in laparoscopic cholecystectomy. Primary outcomes were to spot and specify the unpredictable risk factors and identify the most common intraoperative conversion causes. Secondary outcomes were comparing the impact of each group reasons on conversion rate – patient-related factors, surgeon-related factors and equipment-related and other factors of conversion.